Efficient photosynthesis and economic water use of citrus leaves depend on hybrid, cultivar and leaf type - Zhao, Mingjiong; Liu, Zhenshan; Hu, Yanping; Yi, Shilai; Zhang, Yueqiang; Hu, Bin; Shi, Xiaojun; Rennenberg, Heinz (Frontiers in Plant Science, 2025)
Efficient photosynthesis and economic water use are essential for citrus growth, development and fruit production. The present study was aimed to characterize these processes in current-year spring, autumn, summer and spring shoots of citrus hybrid OP with cultivars ‘Orah’ (OR) and ‘Ponkan’ (PO) and citrus hybrid NT with cultivars ‘Newhall navel orange’ (NO) and ‘Tarocco’ (TA). Cultivars NO and PO show mid-fruit ripening, and cultivars TA and OR late-fruit ripening under field conditions. To characterize photosynthesis and water use, CO2 and H2O gas exchange, water use efficiency and expression of related genes were analyzed. The CO2 and H2O gas exchange parameters measured were determined by hybrid, cultivar and leaf type. Genes involved in lipid and pectin catabolic processes, cell wall biogenesis and modification, carbohydrate and xyloglucan metabolism, cellulose biosynthesis and cell growth were significantly upregulated in current-year spring shoots compared to the other leaf types investigated. Expression of photosynthesis- and transpiration-related genes was significantly enhanced in leaves of late-ripening cultivar OR compared to the other cultivars. These results indicate that the two hybrids of the four citrus cultivars studied differ in the expression of photosynthesis- and transpiration-related genes, but these differences cannot be attributed to fruit maturation.